A comparison of 6-minute walk test distance between asthmatic children and normal healthy children - Gaikwad, Pratibha; Asgaonkar, Bharati; Karande, Bhagyashree; Shah, Shruti (International Journal of Research in Medical Sciences, 2021)
Background: To calculate and compare the six - minute walk test distance between asthmatic children and normal healthy children. Methods: A comparative analysis study was performed to assess the exercise capacity between asthmatic and normal healthy children in the age group of 7 to 12 years. 100 subjects with random sampling were recruited over a period of 1 year according to the inclusion and exclusion criteria, each assigned into 2 groups (n=50). All the Subjects performed the 6MWT successfully and were analysed on parameters like HR, RR, RPE and 6MWTD pre and post-test. Results: Intergroup analysis was done using unpaired t test and level of significance was taken as p<0.05. The results were statistically significant for 6MWTD, HR and RR between asthmatic and normal healthy children, except RPE as no changes were seen in normal healthy children as compared to asthmatic children. Conclusions: Asthmatic children have lower 6MWTD as compared to normal healthy children. This indicates Low exercise capacity in asthmatic children. Additionally, increased HR, RR and RPE were seen in asthmatic children pre as well as post-test.